OVERVIEW OF COMMUNITY STIGMA AND SELF-STIGMA RELATED TO HIV AND AIDS - Aris Tristanto; Afrizal Afrizal; Sri Setiawati; Mery Ramadani (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
Stigma causes PLWHA to experience obstacles in the treatment and care process because people living with stigmatized health conditions are confined to live in the same society, but are still moved and experience their own stigma. Stigma has two understanding points of view, namely community stigma and self-stigma. The stigma of society towards PLWHA occurs at various levels, starting from the family, community, institutional environment, and the mass media. Self stigma (self stigma) is a crisis from people who are stigmatized to apply the stigma to themselves. The general objective is to provide an overview of various cases of stigma against PLWHA from a community perspective and self-stigma. Analysis of this paper is carried out through literature review by examining written sources such as scientific journals, reference books, literature, encyclopedias, scientific essays, and other reliable sources either in written form or in relevant digital formats without going directly to the field. This paper is expected to provide benefits and input, as well as a consideration for decision makers in order to review and determine various policies related to the handling of stigma against PLWHA